2020
DOI: 10.31933/dijemss.v2i1.506
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Firm Value and Its Impact on Stock Prices (Study in Consumer Good Public Companies in Idx 2014-2018)

Abstract: The purpose of this study is to examine and analyze the effect of profitability proxied by Return on Assets (ROA), capital structure proxied by Debt to Asset Ratio (DAR), and Pruchasing Manager Index Manufacture (PMI) on the value of a company that is proxied by Price to Booked Value (PBV) and its impact on Stock Price. The object of this research is the consumer goods companies listed on the Indonesia Stock Exchange period 2014 - 2018. The sample collection technique used was purposive sampling, where 14 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
4
4
0
2
Order By: Relevance
“…The results of this study are in line with the results of research from Bahraini et al (2021) to equity ratio (DER) and total asset turnover ratio (TATO) simultaneously have a significant effect on PBV. 9) The results of the research prove that all independent variables (CR, DER, TATO) simultaneously have a significant effect on the dependent variable of Stock Returns, this is in line with research from (Salim & Firdaus, 2020) which found a significant effect of current ratio and debt to equity ratio on stock returns and research (Sausan et al, 2020) found a significant effect of debt to equity ratio and total asset turnover ratio to stock returns. 10) The results of the calculation of the coefficient of determination R-squared and path analysis prove that the Price to Book Value variable successfully mediates the independent variable so that the indirect effect of the independent variable is more dominant or significant than the direct effect.…”
Section: Direct and Indirect Effectssupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study are in line with the results of research from Bahraini et al (2021) to equity ratio (DER) and total asset turnover ratio (TATO) simultaneously have a significant effect on PBV. 9) The results of the research prove that all independent variables (CR, DER, TATO) simultaneously have a significant effect on the dependent variable of Stock Returns, this is in line with research from (Salim & Firdaus, 2020) which found a significant effect of current ratio and debt to equity ratio on stock returns and research (Sausan et al, 2020) found a significant effect of debt to equity ratio and total asset turnover ratio to stock returns. 10) The results of the calculation of the coefficient of determination R-squared and path analysis prove that the Price to Book Value variable successfully mediates the independent variable so that the indirect effect of the independent variable is more dominant or significant than the direct effect.…”
Section: Direct and Indirect Effectssupporting
confidence: 82%
“…3) The company's ability to manage debt effectively and efficiently compared to the value of its assets will have an impact on the decision of the owners of capital to invest. (Antara, 2012) (-) (Azis et al, 2018) No No No (+) (Bahraini et al, 2021) (-) (+) (-) (Budiharjo, 2015) (+) (Bustani et al, 2021) (+) (Daniswara & Daryanto, 2019) (+) (Djamaluddin et al, 2018) (+) (+) (Elfiswandi et al, 2020) No (+) (Firdaus, 2020) (-) (+) (Hasangapon et al, 2021) (+) (Jang & Utomo, 2021) (+) (Kahfi et al, 2018) (+) (-) (+) (Kuswanto & Taufiq, 2015) (+) (Lumoly et al, 2018) (+) (Majid & Benazir, 2016) (-) (Malebana, 2019) (+) (Manik, 2017) (-) (+) (Murni et al, 2019) (-) (Najmiyah et al, 2014) No No (Nguyen et al, 2021) (-) (Nugroho, 2013) No No No (Nurhasanah, 2013) (+) (Purnamaningsih & Wirawati, 2014) (+) (Putra & Lestari, 2016) (+) (Salim & Firdaus, 2020) (Sausan et al, 2020) (+) (+) (Sinaga, 2014) No (Verawaty et al, 2015) No * Lecturer at Mercu Buana University. ** Profitability.…”
Section: Idx Miningmentioning
confidence: 99%
“…Financial performance has a significant effect on the value of companies listed onJakarta Islamic Index The Indonesian Stock Exchange is acceptable. The results of this research reject research conducted by (Li Jin et al, 2022;Utami et al, 2022), which states that financial performance has no effect on company value and the results of this research are consistent with research by (Irwanti & Ratnadi, 2021;Lukman & Tanuwijaya, 2021;Salim & Firdaus, 2020;Sukesti et al, 2020;Widagdo et al, 2020b;Widyastuti, 2019), which shows that financial performance has a positive and significant effect on company value. Based onsignalling theory that the profitability of a company can be a positive signal for investors.…”
Section: Effect Of Financial Performance On Company Valuesupporting
confidence: 77%
“…Sobel test in this research using application from danielsoper.com that show the impact of the indirect Current Ratio on Firm Value mediated the Dividend Payout Ratio, the value of t count is 3.948426 < 2.00099 t Salim and Susilowati (2020a) showing CR and asset growth have a significant negative effect on firm value. While solvency and profitability have a positive effect, according to research conducted by Anggraeni and Musaroh (2018), which shows that DER has a significant positive effect on firm value, and Salim and Firdaus (2020) also state that ROA has a significant positive effect on not significant effect on firm value. 2) There is a significant positive effect on the Dividend Payout Ratio on the Current Ratio, Debt Equity Ratio, and Return On Assets have a direct partial effect, according to research conducted by Gunawan and Adi (2018) showing that liquidity partially has a positive effect on policy dividends, and Akhmadi and Robiyanto (2020) said that DER had a significant effect on dividend policy, and Budagaga (2017) stated that there was a significant positive ROA relationship between dividend payments and firm value.…”
Section: Analysis Sobel Testmentioning
confidence: 99%